SANKSI PIDANA (ISLAM) DALAM PERSPEKTIF FILSAFAT DAKWAH - Gazali, Ahmad (Alhadharah: Jurnal Ilmu Dakwah, 2017)
Penal sanctions in Islam on more. Because the basic principle of criminal practice in Islamic justice is "better guilty, than punish innocent people". This paradigm may provide a philosophical explanation and Dawah Islamiyah as a forgiving in the judicial process is much more severe, both for criminal actors and other communities. Therefore, the philosophical judgment of Dawah Islamiyah against criminal law in Islam will be able to provide enlightenment in the judicial process in general.